2015
DOI: 10.2147/ijn.s82543
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous bioactive glass surface modified poly(lactic-co-glycolic acid) electrospun fibrous scaffold for bone regeneration

Abstract: A mesoporous bioactive glass (MBG) surface modified with poly(lactic-co-glycolic acid) (PLGA) electrospun fibrous scaffold for bone regeneration was prepared by dip-coating a PLGA electrospun fibrous scaffold into MBG precursor solution. Different surface structures and properties were acquired by different coating times. Surface morphology, chemical composition, microstructure, pore size distribution, and hydrophilicity of the PLGA-MBG scaffold were characterized. Results of scanning electron microscopy indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The regeneration process of bone defects primarily relies on a physical bridge between defect ends and the chemical guidance of bioactive molecules and proteins. Bioactive ceramics have been widely accepted and used as a successful biomaterial in studies of bone repair and drug carriers 1-3, 6, 30, 31, 36-39. Particularly in the bone tissue engineering field, various bioactive factors like DMOG, VEGF and BMP-2 encapsulated in mesoporous bioactive glasses have already been tested to enhance the function of osteogenesis and angiogenesis 3, 6-8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regeneration process of bone defects primarily relies on a physical bridge between defect ends and the chemical guidance of bioactive molecules and proteins. Bioactive ceramics have been widely accepted and used as a successful biomaterial in studies of bone repair and drug carriers 1-3, 6, 30, 31, 36-39. Particularly in the bone tissue engineering field, various bioactive factors like DMOG, VEGF and BMP-2 encapsulated in mesoporous bioactive glasses have already been tested to enhance the function of osteogenesis and angiogenesis 3, 6-8.…”
Section: Discussionmentioning
confidence: 99%
“…New bone formation and vascularization are often limited to the periphery of the scaffolds due to the damaged blood vessels in the center of the defect 4, 5. Methods that aim to address this issue have been explored, including the use of an expensive recombinant pro-angiogenic vascular endothelial growth factor (VEGF) and bone morphogenetic protein (BMP) in combination with tissue engineering scaffolds 6-8. These have strong properties of angiogenesis and osteogenesis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been observed that this effect (i.e., stimulation of angiogenic growth factors) is dose dependent, and high concentration of BG has a negative effect on growth factor secretion. Besides biological properties, surface coating of electrospun PLGA fibers with mesoporous bioactive glass improved the capability of scaffold for BMP-2 delivery (Li et al 2015 ). Addition of BG to collagen has been studied in some research.…”
Section: Introductionmentioning
confidence: 99%